A quest for the assumed LXX Vorlage of the explicit quotations in Hebrews - Steyn, Gert J. (Stellenbosch : Stellenbosch University, 2009)
Thesis (DLitt (Ancient Studies. Biblical Languages))--Stellenbosch University, 2009.